Factors influencing the intentions to purchase Takaful among millennials in Selangor - Nurul 'Afifah, Ahmad (2023)
There is a disturbing tendency among millennials today to their low level of financial awareness that leads to, the intention for takaful is not the top priority to them. Since they are less likely to think about their future, they are not considering takaful, overestimate the cost of purchasing takaful, and are least likely to interact with takaful providers. This study seeks to bridge a knowledge gap regarding the intentions of the millennials in Selangor to purchase Takaful. The factors identified are based on the Theory of Reasoned Action (TRA) and the Theory of Planned Behavior (TPB) which are attitude, knowledge, subjective norms, and religiosity. There are 125 respondents participating in this study. Based on the results of Multiple Linear regression and Pearson correlation Analysis, findings show that attitude and subjective norms are positively and significantly related to purchase intentions. The findings of the study are important for Islamic financial institutions, especially for takaful companies to revamp their marketing strategies. Understanding the behavior of millennials towards takaful could help to strengthen the Takaful products, increase awareness, and make them consider Takaful as one of the options for the future preparations of the next generation.